PERENCANAAN BISNIS DAN PEMBUATAN OLAHAN KERUPUK RUMPUT LAUT “K’SWEED” ANEKA RASA (TINJAUAN ASPEK PEMASARAN) - Muhammad Saipul; Dwi Astuti (Inovbiz: Jurnal Inovasi Bisnis, 2018)
The research was conducted to know the Business Plan And Production Cultivate of Seaweed Crackers Various Flavours, determine the marketing mix, and to know the solution constraints to be implemented on the business of Seaweed Crackers Various Flavours. There are four methods used in implementing part these are preparation plan, implement plan, completion plan and report plan. The preparation stage, the marketing dapartement first thing to do is capital preparation, market a product market survey, preparation of products to be marketed, determination of target, designing and making label until product packaging process. For the time the implementation of this project lasted for three month, starting from 14 march 2017 to 1 may 2017 which took place in the street SMAN 2 Air Putih Village Bengkalis, then subsequently marketed I the district Bengkalis like in outlet KADIN Bengkalis, Evan Swalayan, Mikro Market, Apollo, Swalayan 88 (Plaza Laksmana Bengkalis) and Pesona. Completion of the project Seaweed Crackers Various Flavours this have three variation price is Rp.2.000,-/wrap  for 20 grams, Rp.8.000,-/wrap for 80 grams and Rp.9.000,-/wrap for 100 grams. Project report consists of implementation report of project activities and financial report of project activities.